Study of dynamic changes in the parameters of liver function tests in COVID-19 patients: A hospital-based study in Eastern Nepal - Mittal, Ankush; Farooqui, Mohammad Shamim (Journal of Biomedical Sciences, 2021)
Background: COVID-19 has become a focus of healthcare practitioners worldwide after it was declared as a global pandemic. Although SARS-CoV-2 is primarily affecting the respiratory system, numerous studies have documented its impact on other organ systems, including the liver. This study aims to assess liver function in COVID-19 patients in light of SARS-CoV-2's extremely infectious and pathogenic character. Material and methods: It was a hospital-based retrospective study conducted between January 1, 2021, and July 31, 2021, using data from the Department of Biochemistry at Birat Medical College Teaching Hospital in Nepal. Age, gender, total protein, albumin, AST, ALT, and the AST/ALT ratio were all measured. Results: The median age of COVID-19 patients was 36 years (CI, 25–51), 60 patients (60.0%) were male, 31 patients (31.0%) were obese, and 20 patients (20%) had comorbidities, such as hypertension (14%) and diabetes mellitus (6.0 %). Compared to the non-critical group, the mean values of ALT, AST, ALP, GT, LDH, TBIL, and DBIL were significantly higher in the severe group. On the other hand, total protein and albumin were significantly lower in the severe group than the non-severe group. Conclusion: In COVID-19, aberrant liver function, primarily AST increase, appears to be common. Therefore, direct viral hepatotoxicity during a systemic viral infection must be considered, as well as the possibility of sepsis or worsening of existing liver disease.